The political economy of violence: the case of Venezuela - Leon, Daniel Simon (AUC Knowledge Fountain, 2010)
This thesis will attempt to answer the question of how can the rise in social violence be explained in the oil-rich nation of Venezuela since the 1980s? The once relatively peaceful nation of Venezuela has seen a dramatic rise in social violence over the last three decades that has placed her amongst some of the world's most dangerous countries. A review of the relevant literature will reveal that the study of a social phenomenon such as violence, and in a nation such as Venezuela, is a complicated task because there are a number of different but in many cases interlinked variables that contribute to the formation of this social phenomenon. Therefore the conceptual framework will consist of a multi-variable analysis so that this study may go about to formulate an appropriate explanation based on the complex causes and effects that surround this issue. However, special attention will be given to the nation's developmental history has given way to a severe socio-political crisis. But although special attention will be given to this important variable, no hierarchy of variables will be established as the convoluted nature of social events makes it very difficult to formulate one. Other factors that will also be analyzed as they contribute to the rise of social violence are: the nation's vast hydrocarbon wealth (which is always an outstanding variable because of its economic importance), economic reform and liberalization, and the urbanization process. Although there have been several studies on oil-rich nations (including Venezuela), their economic dynamics, the Latin American urbanization process, and the Venezuelan political crisis, there is an absence of studies that include these intervening factors in a comprehensive manner. This thesis hopes to fill this gap.